Evaluación de la tecnología lidar terrestre (detección y rango de imágenes por medio de láser), para su posible implementación en la integridad de las tuberías para el transporte de Hidrocarburos (2023)
This document intends to present, in a clear and concise way, the results of an investigation carried out during the internship degree option in the Petroleum Engineering career at the University of America, which had the purpose of evaluating the operation of LiDAR technology and its possible implementation in the detection of problems in the hydrocarbon transport pipeline. Thus, the research that was carried out was based on the idea that the fact of being able to use LiDAR technology in the transport of hydrocarbons could facilitate the detection of problems and increase the safety of pipelines. To exemplify this point, it is necessary to mention that the implementation of LiDAR technology can be extremely useful for monitoring hydrocarbon transport pipelines, detecting breakdowns, cuts, environmental problems and with the appropriate addition corrosion. In accordance with the above, it should be noted that the main objective of this research was to evaluate the effectiveness and feasibility of LiDAR technology as an innovative tool to detect potential problems in pipelines and improve their preventive maintenance.